Boron-induced amelioration of aluminium toxicity in a monocot and a dicot species - Corrales, Isabel (Journal of plant physiology, 2008)
Previous research has reported inconsistent results from experiments on the influence of boron (B) on plant sensitivity to potentially toxic aluminium (Al) concentrations. Differences in B requirement and cell wall properties among species, especially between Poaceae and dicots, may account for this. This investigation reports amelioration by B of Al-induced inhibition of root elongation in Al-sensitive cucumber (Cucumis sativus), but not in Al-sensitive maize (Zea mays). Vital staining, however, also revealed a positive influence of B supply on Al tolerance in maize. In both species, adequate B supply decreased Al-induced damage of cell integrity. In cucumber, increasing B supply enhanced Al concentrations and haematoxylin staining in root tips. In maize, no differences for root Al among B treatments were observed. These results indicate that the positive effect of B on Al resistance was not due to less Al accumulation in root tips. Enhanced concentrations of reduced glutathione were found in roots of Al-stressed maize plants growing with adequate B. It is concluded that adequate B supply is essential for prevention of Al toxicity in both the dicot and the monocot species. In dicot cucumber, the B-induced amelioration of root elongation, despite higher Al accumulation in root tips, indicates B-induced change in either or both Al speciation and compartmentation in the tips. The protection by an adequate B supply of roots against Al-induced cell death suggests a role for B in the defence against oxidative stress. This is supported by the observation that Al induced enhanced levels of GSH in roots of maize plants growing with adequate B supply but not in those growing with either deficient or excess B concentrations